PENDAMPINGAN PENGISIAN DAN PELAPORAN SPT PAJAK PENGHASILAN UMKM MELALUI E-FORM - Novianty Novianty; Kusuma Indawati Halim (Jurnal Abdimas Bina Bangsa, 2023)
e-Form is an application for filling out corporate tax returns for all business entities that is easy and practical to use. This application really helps business people to fill out and report corporate tax returns quickly and accurately. The purpose of this community service activity is to increase partners' knowledge about how to report annual income in accordance with applicable tax regulations by using the e-Form application. The implementation of this community service activity was carried out at the Fitri salon in the East Pontianak area. Community service activities begin with field observations and interviews or questions and answers with salon owners. Then proceed with the introduction of the e-Form application, assisting in filling out and reporting corporate annual income through the e-Form application, and proceed with evaluating the results of implementing assistance in filling out corporate annual income through the e-Form application. The results of this community service activity are that partners can increase knowledge about how to use the e-Form application, increase knowledge and tax compliance for partners, and can help partners fill out and report corporate tax returns using the e-Form application